Diversity management for sme internationalization: Orchestrating human resource diversity - Breuillot, Angélique; Bocquet, Rachel; Poussing, Nicolas (Management international / International Management / Gestiòn Internacional, 2022)
Diversity management is a crucial element of organizational performance, yet little is known about its effect on SMEs’ internationalization. Relying on resource-based theory and resource orchestration, this article provides a novel view of the effect of four perspectives on diversity management—resistance, discrimination, access-and-legitimacy, and learning—on the scope of SMEs’ internationalization. With a large sample of SMEs, findings show that diversity management perspectives exert contrasting effects on the scope of internationalization. Only the learning perspective increases the likelihood that SMEs transcend European borders. These insights highlight the value of diversity management for SMEs’ internationalization and provide useful managerial recommendations.